Bronchopulmonary dysplasia and neurobehavioural outcomes at birth and 2 years in infants born before 30 weeks. Issue 2 (23rd August 2022) - Martin, Monika; Smith, Lynne; Hofheimer, Julie A; McGowan, Elisabeth C; O'Shea, T Michael; Pastyrnak, Steve; Carter, Brian Scott; Helderman, Jennifer; Check, Jennifer; Neal, Charles; Roberts, Mary B; Dansereau, Lynne M; et al.
Abstract : Objective: To identify neurobehavioural risks in preterm infants with bronchopulmonary dysplasia (BPD) prior to hospital discharge. Design and patients: Longitudinal study of 676 newborns born before 30 weeks of gestation. Setting: Nine university NICUs affiliated with six universities. All were Vermont Oxford Network (VON) participants. Patients and interventions: Infants were enrolled in the Neonatal Neurobehavior and Outcomes in Very Preterm Infants Study from April 2014 to June 2016. Prospective medical record reviews, VON definitions and criteria, and maternal interviews were used to collect maternal and neonatal medical variables and socioenvironmental data. Main Outcome Measures: NICU Network Neurobehavioral Scale (NNNS) at the time of hospital discharge; Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III) and Gross Motor Function Classification System at 2 years' corrected age. Results: Infants with moderate/severe BPD were less attentive (Wald χ 2 9.68, p=0.008), more lethargic (Wald χ 2 9.91, p=0.007), with increased non-optimal reflexes (Wald χ 2 7.37, p=0.025). Infants with moderate/severe BPD were more likely to have Bayley-III language and motor scores <85 (adjusted OR (aOR) 1.74, 95% CI 1.06 to 2.85, and aOR 2.06, 95% CI 1.10 to 3.85). Infants with both moderate/severe and mild BPD were more likely to have a cerebral palsy diagnosis (aOR 2.96, 95% CI 1.34 to 6.54, and aOR 2.81, 95% CI 1.32 to 5.99). Conclusions: BPD severity presents risks for poor neurodevelopment at NICU discharge and at age 2 years. Early identification of poorly regulated behaviour can provide critical information for early preventive and targeted interventions with potential to improve long-term outcomes. Abstract : In a prospective, multicenter study of infants < 30 weeks GA, BPD severity was associated with neurobehavioral outcomes at the time of hospital discharge as measured by NNNS, and with 2 year outcomes.